Clove Farming Performance in Wawolesea Sub District North Konawe District - Eriksan, Eriksan; Salam, Idrus; Alwi, La Ode (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This study aims to determine the performance of clove farming in the Wawolesea District, North Konawe Regency. This research was conducted from July to September 2019. The population in this study were all farmers/heads of families who planted 110 cloves. The sample was determined by simple random sampling, namely by taking 15% of the total population of 32 respondents. The method used to analyze the data is a qualitative descriptive analysis method. The results showed that the performance of the cultivation/farming subsystem, namely a) land processing by using burnt and without burning, planting with a 5 x 5 m cropping pattern, plant maintenance, with fertilization, carried out in the early rainy season, mid-rainy season and after harvesting, watering done in the morning and evening, making soil terraces, controlling pests and diseases by spraying and harvesting using wooden ladders and bamboo ladders.